An Asperger's guide to public speaking how to excel at public speaking for professionals with autism spectrum disorder - Bergemann, Rosalind (Jessica Kingsley Publishers, 2015)
People with Asperger Syndrome (Autism Spectrum Disorder) often excel at public speaking, but there are key elements that they can find challenging. This book explains how to master public speaking with advice on preparation, delivery, gauging your audience, and surviving post-speech social events - all addressed from a unique Asperger perspective.